Benefits and Challenges to Implement Public-Private Partnerships in Water Infrastructure Development in Zimbabwe - Vyas-Doorgapersad, Shikha; Mutandwa, Hudson (Journal of Economic Development, Environment and People, 2023)
The rationale of the study was built on the water infrastructure challenges in Zimbabwe and the challenges in government policies and capacity that demand the participation of public private partnerships (PPPs) in the development of water infrastructure in Zimbabwe. The study adopted the qualitative research approach, and the information is compiled through literature review. Through conceptual and document analysis of information, the study also recognised that there are challenges in the existing PPP arrangements in Zimbabwe that require improvement for their absolute contribution to the management of water resources in the country. The data generated by this study were used to understand the complexities and contestations in Zimbabwe and enrich the body of knowledge and literature about water-related PPPs. Effective PPPs for improved urban water infrastructure cannot be achieved by chance. Effective PPPs require deliberate efforts and comprehensive reforms. The study, therefore, posits that with an environment conducive to operating PPPs, in addition to proper planning and meticulous implementation, Zimbabwe has a high chance of successfully implementing such partnerships for improved urban water infrastructure.